Evaluating the Acoustic Absorption of Modular Vegetation Systems: Laboratory and Field Assessments Using an Impedance Gun - Valentina Oquendo-Di Cosola; María Ángeles Navacerrada; Luis Ruiz-García; Francesca Olivieri (Buildings, 2025)
Introducing vegetation is an effective strategy for improving air quality and mitigating the heat island effect. Green modules, which consist of modules that support substrates and various plant species, integrate these elements. This study analyzes the acoustic absorption properties of a specific green wall module using an impedance gun and the Scan and Paint method for laboratory and on-site measurements. The impedance gun method is effective for in situ analysis, offering advantages over standardized techniques for inhomogeneous samples. The sound absorption coefficient of the substrate and the effects of different plant species were measured. Key findings reveal that the substrate primarily influences sound absorption, with its coefficient increasing with frequency, similar to porous materials. Vegetation enhances the acoustic absorption of the substrate, depending on coverage and thickness, with 80–90% of absorption attributed to the substrate and 4–20% to vegetation. However, not all dense plant species improve absorption; some configurations may decrease it. Improvement correlates with substrate coverage and vegetation layer thickness, while the impact of plant morphology remains unclear. These findings confirm vegetation’s potential as an acoustic absorption tool in urban settings. Additionally, green walls can enhance acoustic comfort in indoor environments such as offices and schools by reducing reverberation. They also improve air quality and provide aesthetic appeal, making them a multifunctional solution for modern architecture.